The association between statistical shape modeling-defined hip morphology and features of early hip osteoarthritis in young adult football players: Data from the femoroacetabular impingement and hip osteoarthritis cohort (FORCe) study. Issue 3 (September 2022) - van Buuren, M.M.A.; Heerey, J.J.; Smith, A.; Crossley, K.M.; Kemp, J.L.; Scholes, M.J.; Lawrenson, P.R.; King, M.G.; Gielis, W.P.; Weinans, H.; Lindner, C.; Souza, R.B.; et al.
Abstract: Objective: To explore the relationship between radiographic hip shape and features of early hip osteoarthritis (OA) on magnetic resonance imaging (MRI) in young male and female football players without radiographic hip OA. Design: We used baseline data from a cohort of symptomatic and asymptomatic football players aged 18–50 years. Hip shape was assessed on anteroposterior radiographs with statistical shape modeling (SSM) for men and women separately. Cartilage defects and labral tears were graded using the Scoring Hip Osteoarthritis with MRI (SHOMRI) system. We used logistic regression with generalized estimating equations to estimate associations between each hip shape variant, called shape modes, and cartilage defects or labral tears. Results: We included 229 participants (446 hips, 77.4% male). For each sex, 15 shape modes were analyzed. In men, three shape modes were associated with cartilage defects: adjusted odds ratios (aOR) 0.75 (95%CI 0.58–0.97) per standard deviation (SD) for mode 1; 1.34 (95%CI 1.05–1.69) per SD for mode 12; and 0.61 (95%CI 0.48–0.78) per SD for mode 15; and one also with labral tears: aOR 1.30 (95%CI 1.01–1.69) per SD for mode 12. These modes generally represented variations in the femoral neck and subtypes of cam morphology, with and without pincer morphology. For women, there was no evidence for associations with the outcomes. Conclusions: Several hip shape variants were associated with cartilage defects on MRI in young male football players. Specifically, one subtype of cam morphology was associated with both cartilage defects and labral tears. Hip shape was not associated with early OA features in women.